A necessary relationship the development of Anglo-American cooperation in naval intelligence - Soybel, Phyllis L. (Praeger, 2005)
The relationship of the United States and Great Britain has been the subject of numerous studies with a particular emphasis on the idea of a special relationship based on traditional common ties of language, history, and political affinity. Although certainly special, Anglo-American cooperation arose from mutual necessity. Soybel examines the special relationship through a new lens-that of the most intimate of wartime collaborations, the naval intelligence relationship. Rather than looking at the uses of intelligence and espionage, Soybel explores how the cooperation was established and maintained, particularly through the creation of administrative bureaucracies, as well as how World War I and pre-war efforts helped pave the way towards wartime cooperation. The development of the wartime cooperation in naval intelligence between 1939 and 1943 highlights the best and worst of the alliance and shows both its advantages and its limitations. It demonstrates that the Anglo-American partnership during World War II was a necessary one, and its intimacy demanded by the exigencies of the total war then being fought. Its problems were the result of traditional conflicts based on economics, imperial concerns, and national interests. Its successes found their bases in individual partnerships formed during the war, not in the overall one given mythical status by men like Winston Churchill. While still giving credit to the unique alliance that has survived in the last fifty years, this study shows that the close ties were necessary, not special.